Investment and human rights: Is there an elephant in the room? - Anna De Luca; Angelica Bonfanti (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
This Perspective discusses counterclaims of respondent states in investor-state dispute-settlement (ISDS) as effective means to better integrate investment and human rights law. It does so in light of the current UNCITRAL process on ISDS reform, as well as the recent UN treaty project on human rights protection from corporate abuses.
Keywords: 330